Variation in the Human Leukocyte Antigen system and risk for endemic Burkitt lymphoma in northern Uganda. (18th February 2020) - Kirimunda, Samuel; Verboom, Murielle; Otim, Isaac; Ssennono, Mark; Legason, Ismail D.; Nabalende, Hadijah; Ogwang, Martin D.; Kerchan, Patrick; Kinyera, Tobias; Mwebaza, Ivan; Joloba, Moses; Ayers, Leona W.; et al.
Summary: Endemic Burkitt lymphoma (eBL) is an aggressive childhood B‐cell lymphoma associated with Plasmodium falciparum ( Pf ) malaria and Epstein–Barr virus (EBV) infections. Variation in the Human Leukocyte Antigen (HLA) system is suspected to play a role, but assessments using less accurate serology‐based HLA typing techniques in small studies yielded conflicting results. We studied 200 eBL cases and 400 controls aged 0–15 years enrolled in northern Uganda and typed by accurate high‐resolution HLA sequencing methods. HLA results were analyzed at one‐ or two‐field resolution. Odds ratios and 95% confidence intervals (aOR, 95% CI) for eBL risk associated with common HLA alleles versus alleles that were rare (<1%) or differed by <2% between the cases and controls as the reference category, were estimated using multiple logistic regression adjusting for age, sex, microgeography, region, malaria positivity and treatment history, and genetic variants associated with eBL. Compared to the controls, eBL cases had a lower frequency of HLA‐A*02 (aOR = 0·59, 95% CI 0·38–0·91), HLA‐B*41 (aOR = 0·36, 95% CI 0·13–1·00), and HLA‐B*58 alleles (aOR = 0·59, 95% CI 0·36–0·97). eBL cases had a lower frequency of HLA‐DPB1 homozygosity (aOR = 0·57, 95% CI 0·40–0·82) but a higher frequency of HLA‐DQA1 homozygosity (aOR = 2·19, 95% CI 1·42–3·37). Our results suggest that variation in HLA may be associated with eBL risk.